Hubungan Kepemimpinan Qur’ani Kepala Sekolah dan Pendidikan Nilai-Nilai Qur’an dengan Pembentukan Kepribadian Siswa - Rahmi, Agustina; Madihah, Husnul; Sabariah, Sabariah (Sekolah Tinggi Agam Islam Sumatera Medan, 2023)
Efforts to maximize the role of teachers by maximizing the internal and external factors of teachers are well conditioned in order to be able to realize the formation of the personality of students. Factors that are thought to influence the formation of students' Qur'anic personality are the Qur'anic leadership of the principal and Qur'anic value education. This study aims to describe: the relationship between the principal's Qur'anic leadership, Qur'anic values education, and the formation of Qur'anic personality in HSC plus tahfiz in South Kalimantan. The research conducted was descriptive correlation with quantitative approach. In this study the population was 46 HSC plus tahfiz teachers in 2023/2024. The sample was taken as a whole, namely 46 people. Researchers used a Likert scale for data collection techniques with a questionnaire. Data analysis in this study using descriptive statistical analysis and SPSS statistics. The results of the study explained that the principal's Qur'anic leadership, Qur'anic values education, and Qur'anic Memorization Activities were positively and significantly related to the formation of Qur'anic personality at HSC Plus Tahfiz School in South Kalimantan, with a level of relationship of 76.6%. The better the three factors, the more the formation of Qur'anic personality will increase.